2008
DOI: 10.1016/j.cell.2008.08.035
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Factor Environment Defines Distinct Pluripotent Ground States in Novel Blastocyst-Derived Stem Cells

Abstract: SUMMARY Pluripotent stem cell lines can be derived from blastocyst embryos, which yield embryonic stem cell lines (ES cells), as well as the post-implantation epiblast, which gives rise to epiblast stem cell lines (EpiSCs). Remarkably, ES cells and EpiSCs display profound differences in the combination of growth factors that maintain their pluripotent state. Molecular and functional differences between these two stem cell types demonstrate that the tissue of origin and/or the growth factor milieu may be import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
201
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(213 citation statements)
references
References 56 publications
10
201
1
1
Order By: Relevance
“…However, the molecular mechanism that underlies this differential behavior has not yet been clarified. In recent years, pluripotent stem cells at different developmental stages have been identified, such as EpiSCs and FGF/ activin/Bio-stem cells (FAB-SCs) in the mouse [46,47,52]. EpiSCs are derived from the postimplantation epiblast and have similar features to hESCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanism that underlies this differential behavior has not yet been clarified. In recent years, pluripotent stem cells at different developmental stages have been identified, such as EpiSCs and FGF/ activin/Bio-stem cells (FAB-SCs) in the mouse [46,47,52]. EpiSCs are derived from the postimplantation epiblast and have similar features to hESCs.…”
Section: Discussionmentioning
confidence: 99%
“…The cells showed an absence of the human ESC-specific surface makers, SSEA-3 ( Figure 1G) and SSEA-4 ( Figure 1H). The expression of E-cadherin suggests that the oiPSCs are reprogrammed beyond the state of 'near pluripotency' (the state of so-called FAB-SCs) to the state of 'full pluripotency' (the state of ES cells) [25][26][27]. Moreover, RT-polymerase chain reaction (RT-PCR) showed that oiPSCs express many ES cell marker genes, including Oct4, Sox2, Nanog, Tdgf1, Eras, Dnmt3b, Dax1, Dppa4 and Gdf3 (Figure 2A).…”
Section: Sheep Ips Cells Exhibit Typical Es Cell Morphology and Markementioning
confidence: 99%
“…In mouse ES cells, these functions are regulated by LIF and BMP, or GSK3 and MAPK signal pathways, 41,42 but in human ES cells, the combination of bFGF, Activin A or TGF-β and the activation of Wnt signaling pathways is dominant in maintaining pluripotency. [43][44][45] X-chromosome inactivation was one of the most important epigenetic changes during the ES derivation. ICM-derived mouse ES cells have two active X chromosomes (XaXa) and will randomly inactivate one X chromosome upon differentiation (XaXi) through XistRNA coating the inactive X in cis; 46 however, in human, the X chromosome inactivation was pre-determined before blastocyst formation.…”
Section: Discussionmentioning
confidence: 99%